The Influence of The Talking Stick Method on The German Speaking Ability of Class XI Students at Tamansiswa Private High School Pematang Siantar - Adewanti Marbun (MultiTech Publisher, 2023)
This research aims to see the effect of the Talking Stick method on the speaking abilities of class XI students at Tamansiswa Pematang Private High School Siantar. The research method used is Quantitative with Pre- experimental And design study One Group Pretest-Posttest. Population study namely class Xl Tamansiswa Private High School Pematang Siantar with 125 people. Based on Purposive sampling technique, from the population produced 30 people, namely class XI IPA-4 as research sample. The data collection techniques that is form test b text speaks German. By doing steps pretest, treatment by applying the method learning Talking Stick And posttest so generated data study. The average pretest score is 56.67 which is included in the category not good then the average posttest result is 80.00 which is included in the category very Good. Based on results analysis data And hypothesis Which tested, is known that There was an increase in the German speaking skills of class XI students at Tamansiswa Private High School Pematang Siantar with Talking Stick method . Matter This is proven by the results of the normality test analysis with a pre-test score of 0.085 (0.05 < 0.085) and the posttest score was 0.173 (0.05 < 0.173). Then based on the test hypothesis statistics with paired samples test generated mark significance as big as 0.001< 0.05 in meaning of calculated statistical results (number t output) < table statistics (t-table), concluded that Ho rejected And H ₁ accepted . With thereby there is skill improvement speak the language German student class XI Tamansiswa Pematang Private High School Siantar by applying the Talking stick method to class XI IPA-4 students.